Three dimensional simulation of hydrogen chloride and hydrogen fluoride during the Airborne Arctic Stratospheric Expedition - Kaye, Jack A.; Rood, Richard B.; Stolarski, Richard S.; Douglass, Anne R.; Newman, Paul A.; Allen, Dale J.; Larson, Edmund M.; Coffey, Michael T.; Mankin, William G.; Toon, Geoffrey C. (1990)
Simulations of the evolution of stratospheric distributions of hydrogen chloride (HCl) and hydrogen fluoride (HF) have been carried out for the period of the Airborne Arctic Stratospheric Expedition (AASE) with a three-dimensional chemistry-transport model. Simulations were performed assuming only homogeneous gas phase chemistry for HF and both homogeneous gas phase and heterogeneous chemistry for HCl. Results show heterogeneous loss of HCl is needed to provide agreement with infrared column measurements. Estimates of the impact of heterogeneous loss on the global HCl distribution are obtained from the model. Reductions of HCl due to heterogeneous loss are calculated to be localized to regions of high vorticity, even after more than a month of integration.